Psychometric assessment of the Chinese adaptation of the patient participation scale targeting inpatients: a validation research - Zhao, Rui; Huo, Mingshu; Wang, Lei; HuYan, Sihan; Li, Hongyu; Cai, Yan (Frontiers in Psychology, 2024)
Objective The objective of this research was to introduce, translate, and verify the Patient Participation Scale (PPS) within a Chinese context. Methods We applied a combination of internal consistency testing, item analysis, exploratory factor analysis, and confirmatory factor analysis. The research involved 453 individuals, comprising both outpatients and inpatients, across three Jinzhou Medical University-affiliated hospitals in China. Additionally, a subgroup of 50 patients underwent a retest after a 2-week interval to assess reliability. Results The adapted Chinese edition of the PPS included 21 items. Exploratory factor analysis identified four distinct factors, accounting for 66.199% of the total variance. Confirmatory factor analysis supported a suitable four-factor structure (χ/df: 2.045, RMSEA: 0.048, GFI: 0.935, AGFI: 0.914, TLI: 0.958, CFI: 0.965, and PGFI: 0.712). The factor loadings corresponded to each item exceeded 0.6, the average variance extracted (AVE) exceeded 0.5, and the composite reliability (CR) exceeded 0.7. The correlation coefficients stayed below the square root of the AVE, demonstrated relatively favourable convergent and discriminant validity.The Chinese PPS edition demonstrated high internal consistency (Cronbach’s alpha: 0.919), with dimensional Cronbach’s alpha ranged from 0.732 to 0.918. Split-half as well as retest reliabilities were recorded at 0.737 and 0.864, respectively. The content validity index for the Chinese PPS edition stood at 0.974. Conclusion The Chinese edition of the PPS emerges as a valid and reliable tool for assessing patient engagement in their own treatment as well as care, applicable in both inpatient as well as outpatient settings.